Audit Kepatuhan Terhadap Pelaksanaan Program Keadilan Transisi Bagi Korban Paska Konflik Untuk Komisi Kebenaran Dan Rekonsiliasi Aceh (KKR Aceh) (Studi Kasus Pada Yayasan Tifa) - Hartini, Supri; Achyarsyah, Padri (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study was to determine compliance with the implementation of the Transitional Justice program for Post-Conflict Victims for the Aceh Truth and Reconciliation Commission at the Tifa Foundation. The method used in this research is a qualitative method with a case study approach. This study uses primary data that was obtained from Tifa Foundation directly through document collection and interviews with resource persons. Data analysis was carried out together with data collection by determining compliance criteria and processing data using working papers to draw conclusions from the research. Based on the results of this study, it shows that the level of compliance of the Tifa Foundation in implementing the program reaches 98% so that it can be said to be very good.